Analysis of the World Championships 1997 in Freestyle and Greco-Roman wrestling with regards to the FILA Summit - Tünnemann, H.
0 Preface 1 Analyses of strategy 2 Country specific aspects 3 Individual analyses 4 Analysis of the Juniors World Championships 1997 5 Country specific aspects of the Juniors World Championships 6 Individual analyses of the Juniors World Championships 7 Conclusions